2016
DOI: 10.3390/ijerph13111061
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Street Audits to Understand the Walkability of Older Adults’ Route Choices by Gender and Age

Abstract: Walking for physical activity can bring important health benefits to older adults. In this population, walking has been related to various urban design features and street characteristics. To gain new insights into the microscale environmental details that might influence seniors' walking, details which might be more amenable to change than neighbourhood level factors, we employed a reliable streetscape audit tool, in combination with Google Street View™, to evaluate the 'walkability' of where older adults cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Our study contributes to the nascent body of literature utilizing GSV to implement virtual neighborhood audits for neighborhood features such as walkability,(Brookfield and Tilley, 2016) physical disorder,(Mooney et al, 2014) retail alcohol stores,(Less et al, 2015) and urban greenery,(Li et al, 2015) Researchers have also implemented computerized approaches to label images for pedestrian count(Yin et al, 2015) and visual enclosure (i.e., proportion sky visible from a point on the street)(Yin and Wang, 2016)—measures that are connected with walkability. A previous study found Google's Computer Vision API to be effective at characterizing the naturalness of urban areas with GSV images from the city of Edinburgh.…”
Section: Discussionmentioning
confidence: 95%
“…Our study contributes to the nascent body of literature utilizing GSV to implement virtual neighborhood audits for neighborhood features such as walkability,(Brookfield and Tilley, 2016) physical disorder,(Mooney et al, 2014) retail alcohol stores,(Less et al, 2015) and urban greenery,(Li et al, 2015) Researchers have also implemented computerized approaches to label images for pedestrian count(Yin et al, 2015) and visual enclosure (i.e., proportion sky visible from a point on the street)(Yin and Wang, 2016)—measures that are connected with walkability. A previous study found Google's Computer Vision API to be effective at characterizing the naturalness of urban areas with GSV images from the city of Edinburgh.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have used Google Street View to perform virtual audits to assess walkability, 27 physical disorder, 28 retail alcohol stores 29 and urban greenery 30 among other neighbourhood characteristics. Researchers have also developed a Computer Assisted Neighborhood Visual Assessment System to allow users to conduct virtual neighbourhood audits of Google Street View images.…”
Section: Discussionmentioning
confidence: 99%
“…Accounting for available programming and activities fostering social support and interaction, such as clubs and groups, would similarly be useful (Diaz Moore 2014). OWI combines an audit with a survey, and it is also possible to combine with geospatial data such as Google Street View (Brookfield and Tilley 2016). This kind of integration is promising.…”
Section: Whatmentioning
confidence: 99%